Kasus mastitis sub klinis pada sapi perah laktasi di Kecamatan Pujon Kabupaten Malang - Lili Zalizar; sujono sujono; Dian Indratmi; Yovi A Soedarsono (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
The purpose of this research was to find out how much cases of subclinical mastitis in Pujon district, Malang regency. This research was conducted in Pujon District of Malang Regency by using survey method. The inclusion criteria of farmers is minimum 2 (two) years of dairy cows. As many as 110 tail of lactation dairy cows from Maron Sebaluh hamlet in Pandesari village and 103 tail of Bakir hamlet in Sukomulyo village were examined against mastitis by using California Mastitis Test (CMT). In addition, direct observation of post-milking treatment and ownership of biogas digesters and as well as interviews using questionnaires was conducted to support data. Data were analyzed descriptively and by using simple statistics. The results showed that in Maron Sebaluh the percentage of cows with subclinical mastitis reached 58.18%, 10.00 % of clinical mastitis and 31.82% negative. Whereas in Bakir, subclinical mastitis reached 59.22%, clinical mastitis 0.97% and 39.81% negative. The number of cows that suffered from mastitis (subclinical and clinical) and got the treatment of dipping post-milking with antiseptic is only 28 cows, fewer than that treated with rinse water, 107 cows. Ownership of biogas digester will not automatically reduce the case of mastitis since the behaviour of farmers in keeping barn hygiene is not maintained. Every position of cow’s teat have risk to be infected by microorganisms that caused mastitis.